Efficacy and Safety of Bimatoprost 0.01% for the Treatment of Eyebrow Hypotrichosis: A Randomized, Double-Blind, Vehicle-Controlled Study - Poonkiat Suchonwanit (2020)
BACKGROUND: Eyebrow hypotrichosis is an important dermatological problem. However, there is no standard treatment. OBJECTIVE: To study the efficacy and safety of bimatoprost 0.01% for the treatment of eyebrow hypotrichosis. MATERIALS AND METHODS: Although bimatoprost 0.03% has been studied previously, this is the first study to evaluate the efficacy and safety of bimatoprost 0.01% for the treatment of eyebrow hypotrichosis. A randomized, double-blinded, vehicle-controlled trial was conducted in 40 patients. All patients were randomized to receive bimatoprost 0.01% or placebo vehicle, once daily, for 6 months. The primary outcome was improvement in eyebrow density and diameter. Additional outcomes were the improvement in clinical assessments and safety evaluation. RESULTS: Compared to the vehicle group, bimatoprost 0.01% significantly increased mean eyebrow hair density, eyebrow hair diameter, and clinical assessments (p < .001) in the drug group. Patients' satisfaction score was higher for the drug group than the vehicle group (p < .05). Adverse effects of the treatment were minimal and similar between the 2 groups. CONCLUSION: Bimatoprost 0.01% was found to be superior to a placebo for eyebrow enhancement. Bimatoprost 0.01% can be considered effective, safe, and well-tolerated for the treatment of eyebrow hypotrichosis.